Pembelajaran Huruf - Huruf dan Angka Bahasa Arab Saat Pandemi Covid – 19 Melalui Smart Card - Binersa, Ixora Latifolia; Pratiwi, Lisa; Susetya, Bayu Adi (CITRAWIRA : Journal of Advertising and Visual Communication, 2021)
Smart cards are a medium for children's learning that integrates interesting games, media creativity and promotes interaction between family members. This smart card has the theme of hijaiyah letters as an educational medium in learning Arabic numbers and letters during the pandemic that is happening in Indonesia. Now a lot of new innovations are created because of this pandemic period. This method is necessary because direct learning of Arabic letters and numbers is being avoided during the pandemic. This smart card is here to be an alternative for children to study at home. Based on the analysis conducted on the literature review, based on this incident led to the emergence of new obstacles in the way of educating children, namely the difficulty of parents in accompanying children to study at home due to a lack of understanding of the material by parents. With this smart card, it is hoped that children will have no difficulty in learning hijaiyah numbers and letters even though there is a companion